2001
DOI: 10.1016/s0895-7061(01)02206-3
|View full text |Cite
|
Sign up to set email alerts
|

Aortic smooth muscle cell proliferation and endothelial nitric oxide synthase activity in fructose-fed rats

Abstract: The aim of this study was to evaluate the proliferative behavior of vascular smooth muscle cells in primary culture (pC-SMC) and the endothelial nitric oxide synthase (eNOS) activity in the endothelial lining of the aorta of fructose-fed rats (FFR). This is an experimental model of syndrome X, a cluster of cardiovascular risk factors including hyperinsulinemia, insulin resistance, and hypertension that has been suggested to be of pathophysiologic importance for the development of atherosclerosis. Male Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 33 publications
1
48
1
Order By: Relevance
“…7,21 Furthermore, hyperinsulinemia could activate the sympathetic nerve system, which in turn will elevate the BP. 26 These observations demonstrate that the existence of a functional sympathetic nervous system is required for the development of elevated BP and plasma insulin levels in fructose-fed rats. 27 Furthermore, in a clinical setting, derangements of the peripheral endothelial NO system have been related to the development of hypertension.…”
Section: Discussionmentioning
confidence: 73%
“…7,21 Furthermore, hyperinsulinemia could activate the sympathetic nerve system, which in turn will elevate the BP. 26 These observations demonstrate that the existence of a functional sympathetic nervous system is required for the development of elevated BP and plasma insulin levels in fructose-fed rats. 27 Furthermore, in a clinical setting, derangements of the peripheral endothelial NO system have been related to the development of hypertension.…”
Section: Discussionmentioning
confidence: 73%
“…It has been reported previously that reduced eNOS function may underscore cardiac and smooth muscle atherogenesis in fructose-induced insulin resistance and metabolic syndrome [37]. Recent evidence from our laboratory revealed that gene delivery of eNOS into cardiomyocytes directly improved cardiac contractile function through a phosphatidylinositol-3-kinase-dependent mechanism [35].…”
Section: Discussionmentioning
confidence: 82%
“…Actions of ANG II in this model are associated with the development of hypertension, suppression of adiponectin secretion (26), increase of adipocyte size (9), and generation of oxidative stress (32). In addition, blockade of ANG II abolished the increased VSMC proliferation, restored eNOS activity (19), and improved the insulin sensitivity (11). Since hyperuricemia is associated with activation of RAS (18,21), it is tempting to speculate that increased synthesis of ANG II in this model could be secondary to the rise of plasma uric acid.…”
Section: Discussionmentioning
confidence: 89%